1989
DOI: 10.1159/000171889
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Resection in Adults: Causes and Consequences

Abstract: We reviewed the records of 160 adult patients undergoing intestinal resection to determine the outcome of this surgical procedure. Twenty-three patients (14%) underwent massive ( > 50%) resection and 18 developed the short bowel syndrome. Mesenteric vascular disease was the indication for resection in 16 (70%) of these patients. The most frequent indications for resection in the 137 patients (86%) undergoing less extensive resection were: obstruction (26%); tumor (23%); Crohn’s disease (22%), and trauma (10%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
1
0
1
Order By: Relevance
“…Haymond reported that in 1935 his operative mortality was 33%, and only 20% of the patients survived 1 year [3]. More recent estimates suggest that at least 70% of patients with the short bowel syndrome now leave the hospital, and almost all of this group are alive at the end of 1 year [9]. Indeed, progress has been made.…”
mentioning
confidence: 99%
“…Haymond reported that in 1935 his operative mortality was 33%, and only 20% of the patients survived 1 year [3]. More recent estimates suggest that at least 70% of patients with the short bowel syndrome now leave the hospital, and almost all of this group are alive at the end of 1 year [9]. Indeed, progress has been made.…”
mentioning
confidence: 99%
“…Πλέον, µεγάλος αριθµός ασθενών µε µικρό µήκος λεπτού εντέρου (<50 cm) είναι απεξαρτηµένοι από την παρεντερική θρέψη, µε την εφαρµογή θεραπειών ενίσχυσης της απορρόφησης. Από το 1935 και τις επιβιώσεις της σειράς του Haymond, µε 33% µετεγχειρητική επιβίωση και 20% επιβίωση ενός έτους, έχουµε φτάσει σήµερα σε επιβίωση ασθενών µε βραχύ έντερο 70% και επιβίωση πρώτου έτους περίπου 100%(12). Τέλος, η µεταµόσχευση του εντέρου εξελίσσεται για να προσφέρει λύση σε επιλεγµένους ασθενείς µε σύνδροµο βραχέος εντέρου όταν τα υπόλοιπα υποστηρικτικά µέτρα έχουν αποτύχει.Το σύνδροµο βραχέος εντέρου είναι ένα σύνθετο σύνδροµο που ακολουθεί τη µεγάλης έκτασης εντερική εκτοµή, εφόσον ανεπαρκεί η απορροφητική επιφάνεια του εναποµείναντος λεπτού εντέρου.…”
unclassified